A Case of Plasma Cell Granuloma of Unknown Cause - Imran, Faizuddin; Rajan, Sukanya; Vijay, Geetha (Journal of Orofacial Research, 2012)
Plasma cell gingivitis (PCG) is a condition in which a hypersensitive reaction is seen to various etiologic causes in the gingival tissue. A rare form of PCG, called plasma cell granuloma may sometimes occur, in which enlargement of a specific area of the mouth is seen. This case report elicits a case of such a rare case of the granuloma in the anterior maxilla of a 25-year-old patient.